Analysis of Variable Strain Amplitude Response Caused by Impact Loading of Carbon Nanotube Reinforced Magnesium Alloy AZ31B. (2015) - Abdullah, M.F.; Abdullah, S.; Omar, M.Z.; Sajuri, Z.; Risby, M.S.
Abstract: This paper presents the effects of carbon nanotubes (CNT) in the AZ31B magnesium alloy when loaded by impact tests associated to transient-based variable amplitude (VA) loadings. The failure behaviors of this alloy, as well as the effects of varying percentages of added carbon nanotubes (CNTs) on the absorption energy of the alloys under transient variable amplitude load impact signal were investigated thoroughly via both experiment and simulation. The CNT composition of 0.1, 0.2, and 0.5 by percentage weight of CNT in AZ31B were chosen as the specimen preparation. The Charpy testing was then used to record the impact behavior of the specimens. In addition, a strain gauges was attached on each specimen during the test in order to record the affected variable amplitude strain signals for both specimen and also the Charpy striker. Using the signal processing analysis for VA strain loading, the power spectrum density approach was used for determining the energy-based distribution. To obtain this type of energy, the VA strain signals were converted from the time domain to a frequency domain using the Fast Fourier Transform method. Significantly, the signal analysis showed that the AZ31B magnesium alloy with 0.2% CNT absorbed the highest amount of energy among the tested specimens. Therefore, addition of an optimal amount of CNTs improves the strength of alloys.